Poor adult tuberculosis treatment outcome and associated factors in Gibe Woreda, Southern Ethiopia: An institution-based cross-sectional study - Melkamu Merid Mengesha; Mathewos Alemu Gebremichael; Desta Watumo; Inger Kristensson Hallström; Degu Jerene (PLOS Global Public Health, 2022)
Tuberculosis (TB) remains a major medical and public health problem throughout the world, especially in developing countries including Ethiopia. Its control program is currently being challenged by the spread of drug-resistant TB, which is the result of poor treatment outcomes. Hence, this study assessed poor adult TB treatment outcomes and associated factors in Gibe Woreda, Southern Ethiopia. An institution-based cross-sectional study was conducted from March 1, 2020 to March 30, 2020, using a standard checklist to review clinical charts of TB patients who enrolled on first-line TB treatment under DOTS between June 2016 and June 2019. Poor treatment outcomes constituted death during treatment, treatment failure, and loss to follow-up (LTFU). Descriptive statistics were used to describe the characteristics of study participants. A binary logistic regression model was fitted to identify factors influencing treatment outcome and adjusted odds ratios with a 95% confidence interval were reported. The statistical significance of all tests in this study was declared at P-value <5%. A total of 400 adult TB patients were participated. The mean age of study participants was 39.2±16.7 years, 55.5% were males and 79.8% were pulmonary tuberculosis cases. Regarding the treatment outcomes, 58% completed treatment, 27.5% cured, 9.3% were LTFU, 3.2% died, and 2.0% failed. The overall poor treatment outcome was 14.5% (95% CI: 11.1–17.9). Age (aOR = 1.02; 95%CI: 1.01–1.04), male gender (aOR = 1.82; 95% CI: 0.99–3.73), travel ≥ 10 kilometres to receive TB treatment (aOR = 6.55; 95% CI: 3.02–14.19), and lack of family support during the course of treatment (aOR = 3.03; 95% CI: 1.37–6.70), and bedridden baseline functional status (aOR = 4.40; 95% CI: 0.96–20.06) were factors associated with poor treatment outcome. Successful TB treatment outcome in this study area was below the national TB treatment success rate. To improve positive treatment outcomes, remote areas should be prioritized for TB interventions, and stakeholders in TB treatment and care should give special emphasis to adults over the age of 45 years, males, those who travel more than 10 kilometres to receive TB care, having bedridden baseline functional status and those who had no family support.